Clinical case of treatment of chlamydial-candidiasis mixed infection of the vagina and cervix - Ostashevska, Viktoriia; Beniuk, Vasyl; Shcherba, Olena; Kovaliuk, Tetiana; Lastovetska, Liliia (The Ukrainian Scientific Medical Youth Journal, 2025)
this clinical case demonstrates the successful treatment of a patient with chlamydial-candidiasis mixed infection of the vagina and cervix. During the clinical and laboratory examination of the urogenital contents, a violation of the vaginal microbiocenosis was detected, yeast-like fungi of the genus Candida and Chlamydia trachomatis DNA were verified. Immunological examination showed an increased content of antichlamydial and anticandidiasis immunoglobulins M and G and a decrease in the content of lysozyme in cervical mucus. The patient was prescribed outpatient drug treatment. The complex of drugs included a macrolide antibiotic from the azalide group, an antifungal agent from the triazole group, an inducer of the synthesis of endogenous α- and γ-interferons, a local combined antiseptic preparation containing chlorhexidine bigluconate and dexpanthenol, and a probiotic containing lacto- and bifidobacteria. After the course of treatment, the patient's condition improved, the elimination of Candida fungi and Chlamydia trachomatis was observed, the vaginal microbiocenosis was normalized; the titers of both antichlamydial and anticandida immunoglobulins decreased by 2 times and the level of lysozyme in cervical mucus increased. During the year of observation, no relapses were detected. The uniqueness of the mixed infection of Candida albicans and Chlamydia trachomatis lies in the fact that the clinical symptoms are erased, since the properties of individual pathogenic organisms do not add up, and a fundamentally new pathogenetic mechanism of disease development arises. This significantly complicates diagnosis and treatment. That is why we have selected a combination of drugs that contribute to the destruction of both pathogens, normalize the vaginal microflora and restore local immunity of the vaginal mucosa and cervix, which provides a stable therapeutic effect and prevents possible relapses. Particular attention was paid to an individual approach to treatment, which included an assessment of concomitant diseases, the level of immune defense and the characteristics of the vaginal microbiocenosis in a particular patient. Thus, this case demonstrates the high effectiveness of complex therapy for chlamydial-candidiasis mixed infection, which is based on modern principles of etiotropic and pathogenetic treatment, takes into account the characteristics of the microbial composition and the state of local immunity. This approach allows achieving stable remission and improving the patient's quality of life. The success of our treatment lies in the fact that with the complete elimination of pathogens, especially in the chronic recurrent course of Chlamydia trachomatis, it became possible to prevent negative complications of this disease, namely the tubo-peritoneal factor of infertility, which allows the patient to realize her reproductive plans in the future.